Climate crisis, central banks and the IMF reform - Chmielewska, Anna; Sławiński, Andrzej (Economics and Business Review, 2021)
This paper explores some of the ways in which international central banking can contribute to containing the imminent worldwide climate crisis in a context in which the role of national central banks is important but effectively limited to employing two new stabilization policy tools: macroprudential policy and QE programmes. The authors argue in favour of institutional reform that would gradually transform the IMF into an international central bank and the SDR into a genuine international currency. Even its limited scope would substantially increase the IMF’s capacity to solve one of the key problems of the global climate policy, namely the shortage of funding for the decarbonization of developing economies.